PENGUATAN TOLERANSI MENGHARGAI PERBEDAAN SEBAGAI LANDASAN KEPEMIMPINAN PADA OSIS SMP NEGERI 16 JAKARTA SELATAN - Urasni, Urasni; Muliani, Anggita; Amalia, Aam; Handayani, Fitri; Arief, Erwan Nur; Saefudin, Dwi Akhmad Fauzan (Yayasan Education and Social Center, 2024)
Distribution of Indonesia's population with 1,340 ethnic groups on 17,000 islands with 269,603.4 million people. In terms of the proportion of the population, the male gender is 135,337.0 million people, while the female gender is 134,266.4 million people. This spike provides a distinctive pattern and variety. The diversity of society is fulfilled by the presence of the concept of Bhinneka Tunggal Ika which contains content tolerance. Having tolerance as the main pillar of unity and unity is one of the important characteristics possessed by a leader in achieving goals. The existence of a tolerant leader is needed in every organization such as the Intra-School Student Organization (OSIS) at SMP Negeri 16 South Jakarta. The method used in implementing community service activities is strengthening the character of tolerance and structured assistance. As a result of this activity, students at SMP Negeri 16 South Jakarta, especially members of the OSIS class VIII students, received a lot of information and education about tolerance and leadership and became more familiar with the benefits of tolerance, elements of leadership and leadership styles. Apart from that, it is hoped that this activity can motivate students to implement the character of tolerance more broadly by appreciating and respecting and recognizing the existence of human rights in the life of the nation and state.